2007
DOI: 10.1093/aje/kwm280
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adult Body Mass Index and Height with Anxiety, Depression, and Suicide in the General Population: The HUNT Study

Abstract: A prospective cohort of 74,332 men and women was used to investigate the association of body mass index and height with suicide, anxiety, and depression. Participants in the Nord-Trøndelag Health Study (Norway, 1984-1986) (HUNT 1) were aged 20 years or more and followed up until December 31, 2002. Anxiety and depression were measured with the Hospital Anxiety and Depression Rating Scale (HADS) in 1995-1997. There were 183 suicides. Suicide risk decreased with increasing body mass index at baseline (1984-1986) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
168
5
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(194 citation statements)
references
References 41 publications
20
168
5
1
Order By: Relevance
“…After adjustment for all these variables, the associations between depression/anxiety and BMI levels remained significant in this study, which is consistent with the findings of most recent studies. [7][8][9][10][11][12][13][14][15] Moreover, our results agree with the earlier studies in that the mental disorder status or its association with BMI levels varies by gender. 7,20,28,29,40 However, our results differed from those of several other studies that have reported no relationship 26 or an inverse association of overweight/obesity with mental disorders in men.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After adjustment for all these variables, the associations between depression/anxiety and BMI levels remained significant in this study, which is consistent with the findings of most recent studies. [7][8][9][10][11][12][13][14][15] Moreover, our results agree with the earlier studies in that the mental disorder status or its association with BMI levels varies by gender. 7,20,28,29,40 However, our results differed from those of several other studies that have reported no relationship 26 or an inverse association of overweight/obesity with mental disorders in men.…”
Section: Discussionsupporting
confidence: 92%
“…3 A growing body of evidence has shown that obesity, highly prevalent and increasing in the United States and worldwide, [4][5][6] is associated with an increased risk of developing psychiatric disorders. [7][8][9][10][11][12][13][14][15] However, most of the earlier studies failed to evaluate the effects of obesity-related comorbidities (ORCs), lifestyle factors (such as smoking, alcohol drinking and physical activity) or other psychosocial factors (such as general health status, emotional support and life satisfaction) on mental health simultaneously, although these factors also affect mental health status 13,[16][17][18][19] or are associated with mental disorders. 16,[20][21][22][23][24][25] On the other hand, some other studies have found no relationship 26 or an inverse association of overweight/obesity with mental disorders in men.…”
Section: Introductionmentioning
confidence: 99%
“…We found three additional studies through bibliography hand-searches, yielding 16 relevant publications for this systematic review. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Inter-rater agreement was good for study screening (kappa statistic 0.72, 95% CI: 0.57-0.87) and for quality assessment (kappa 0.75, 95% CI: 0.62-0.88). Tables 1 and 2 summarize the characteristics and main findings of the prospective and cross-sectional studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This impression is supported by a few studies (Deaton & Arora, 2009; Krayer, Ingledew, & Iphofen, 2008; Rees et al, 2009; Visser-van Balen, 2005). Contrary to this, the findings by Kelnar (2012) and Bjerkeset et al (2008) have not shown any association between shorter stature in adolescents/adults and their mental capacities. This perception is another topic that needs to be reflected on.…”
Section: Discussionmentioning
confidence: 66%
“…(Case & Paxson, 2008; Cheung et al, 2013; Deaton & Arora, 2009; Lee et al, 2009; Magnusson et al, 2005; Rees, Sabia, & Argys, 2009; Samaras, 2012; Balen, Sinnema, & Geenen, 2006; Balen et al, 2005). However, these associations could be related to other stressful stimuli (Bjerkeset, Romundstad, Evans, & Gunnell, 2008; Kelnar, 2012). …”
Section: Introductionmentioning
confidence: 99%